2011
DOI: 10.1007/s13644-011-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Psychological Health among Clergy Serving in the Presbyterian Church (USA): Testing the Idea of Balanced Affect

Abstract: Drawing on the classic model of balanced affect, the Francis Burnout Inventory (FBI) conceptulises good work-related psychological health among clergy in terms of negative affect being balanced by positive affect. In a random sample of 744 clergy (539 clergymen and 205 clergywomen) serving in The Presbyterian Church (USA), negative affect was assessed by the Scale of Emotional Exhaustion in Ministry (SEEM) and positive affect was assessed by the Satisfaction in Ministry Scale (SIMS). At the same time, burno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 50 publications
(70 reference statements)
9
52
0
Order By: Relevance
“…Fifth, the earlier study reported by Francis, Village, Robbins and Wulff (2011) confirmed the construct validity of the balanced affect model of work-related psychological health among a sample of 744 clergy serving in The Presbyterian Church (USA), employing the two measures of positive affect and negative affect proposed by Francis, Kaldor, Robbins, and Castle (2005): the Scale of Emotional Exhaustion in Ministry (SEEM) and the Satisfaction in Ministry Scale (SIMS). The fact that the present study has come to the same conclusion using two very different measures of positive affect (SIMLI) and negative affect (EEMLI) adds further confirmation of the basic theory of the balanced affect approach to clergy work-related psychological health and suggests that the theory is sufficiently robust to be operationalised through a variety of instruments.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Fifth, the earlier study reported by Francis, Village, Robbins and Wulff (2011) confirmed the construct validity of the balanced affect model of work-related psychological health among a sample of 744 clergy serving in The Presbyterian Church (USA), employing the two measures of positive affect and negative affect proposed by Francis, Kaldor, Robbins, and Castle (2005): the Scale of Emotional Exhaustion in Ministry (SEEM) and the Satisfaction in Ministry Scale (SIMS). The fact that the present study has come to the same conclusion using two very different measures of positive affect (SIMLI) and negative affect (EEMLI) adds further confirmation of the basic theory of the balanced affect approach to clergy work-related psychological health and suggests that the theory is sufficiently robust to be operationalised through a variety of instruments.…”
Section: Resultsmentioning
confidence: 62%
“…In a study conducted among clergy serving in The Presbyterian Church (U.S.A.), Francis, Village, Robbins, and Wulff (2011), set out to test the balanced affect model of clergy work-related psychological health. The strategy adopted by this study examined the incremental impact on independent measures of burnout of the interaction term created by the product of the two measures of negative affect and positive affect after taking into account the impact of these two factors considered separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal consistency reliability and construct validity of the two component scales of the Francis Burnout Inventory have been recently tested and supported in a study by Francis, Village, Robbins, and Wulff (2011). More importantly, this study has tested and supported the balanced affect model of work-related psychological health by demonstrating how high levels of positive affect serve to offset high levels of negative affect in order to maintain a form of psychological equilibrium.…”
Section: Work-related Psychological Healthmentioning
confidence: 69%
“…Inventory and the psychometric properties of the instrument led to a reconceptualization of burnout in terms of the two dimensions proposed by the balanced affect model of psychological wellbeing (Bradburn, 1969) and operationalised in the Francis Burnout Inventory: positive affect measured by the Satisfaction in Ministry Scale and negative affect measured by the Scale of Emotional Exhaustion in Ministry (Francis, Kaldor, Shevlin, & Lewis, 2004;Francis, Kaldor, Robbins, & Castle, 2005;Francis, Village, Robbins, & Wulff, 2011). A series of studies reported on the application of the Francis Burnout Inventory in the UK Brewster, Francis, & Robbins, 2011;Francis, Gubb, & Robbins, 2012;Randall, 2013;Francis, Payne, & Robbins, 2013).…”
Section: Discontent With Both the Theoretical Model Underpinning The mentioning
confidence: 99%